O EFEITO TARDIO DA PRÁTICA DA AMAMENTAÇÃO NA DENSIDADE MINERAL ÓSSEA DE MULHERES NA PÓS-MENOPAUSA: REVISÃO SISTEMÁTICA DE ESTUDOS OBSERVACIONAIS - Adriany Cristine Santos Gonçalves (Universidade do Estado do Rio de Janeiro, 2014)
Breastfeeding is a period of intense bone mobilization for milk production. During this phase, womensuffer a great loss of bone mass with evidence of recovery after weaning. Currently this has been a worryingperiod in woman's life as there are suspicions that bone loss during lactation generates a late effect on bonemineral density (BMD) when this woman is postmenopausal. The reduced BMD is a major risk factor forosteoporosis that affects around 200 million women over fifty years worldwide. The aim of this study wasto evaluate the effect of breastfeeding on bone mineral density in postmenopausal women. For this, weperformed a systematic literature review. The search for articles in databases (Lilacs, Medline via Pubmedand Scopus) were supplemented by manual checking of references. It was identified a total of 181 articlesand, after applying the inclusion criteria, 24 articles were selected for the systematic review. The resultsof several studies are divergent concerning methodological issues, classification of breastfeeding duration,for the variables that cause confusion, age group and ethnicity, which makes comparisons between themdifficult. Part of the studies relates some kind of effect (positive or negative) while another part shows, themost frequently, the observation of an inverse correlation between breastfeeding and bone mineral densityin postmenopausal. However, when other variables (number of pregnancies, age, time since menopause, etc.)are considered in the analysis in conjunction with breastfeeding, the latter loses significant relationship. Morestudies with better methodological rigor are still necessary to evaluate if indeed the effect can be attributedto breastfeeding or other factors that are also related to bone mineral density in postmenopausal women. DOI 10.12957/demetra.2014.10832